War and empire : the American way of life - Atwood, Paul L. (Pluto Press, 2010)
"In this provocative study, Paul Atwood attempts to show Americans that their history is one of constant wars of aggression and imperial expansion. The book shows that, far from being dragged reluctantly into foreign entanglements, America's leaders have always picked its battles in order to increase their influence and power, with little regard for the American soldiers and 'enemy' civilians killed or made to suffer in the process."--Jacket.